Strategic conflict - Canary, Daniel J.; Lakey, Sandra (New York, NY : Routledge, 2013)
'Strategic Conflict offers a research-based, accessible analysis of how people can manage conflict productively. Moving beyond the basics of conflict, it examines interpersonal situations in which conflict occurs and promotes strategic communicative responses based on the latest theoretical research. Daniel J. Canary and his colleagues add personal observations, media examples, and samples of actual interaction to provide concrete illustrations of the research findings. This comprehensive volume provides students with the tools to understand conflict in real-world contexts.' -- Publisher's website.
Includes bibliographical references and index.
Keywords: Interpersonal conflict; Interpersonal communication; Conflict management